EVALUATION OF PARKING SITUATION IN PRESOV AND NITRA (Perner's Contacts, 2018)
This paper is about current state of parking problem in two different housing estates. We have done a traffic survey in housing estate Klokocina situated in city of Nitra and similar survey in housing estate Sekcov in Presov. We have counted cars, which parked on the streets and also parking spaces. City offices in both cities had given us the necessary documentation about numbers of registered cars and flats in these areas. The results from traffic survey are alarming. The car parks have insufficient capacity and many cars stop at forbidden or dangerous areas of the streets. This paper includes results, which were used as a base data for transport planning. We have focused on the most critical areas of housing estates, where the problem with parking was emerged.
Keywords: parking, car park, traffic engineering, road transport, city